2015
DOI: 10.1038/onc.2015.427
|View full text |Cite|
|
Sign up to set email alerts
|

RAD18, WRNIP1 and ATMIN promote ATM signalling in response to replication stress

Abstract: The DNA replication machinery invariably encounters obstacles that slow replication fork progression, and threaten to prevent complete replication and faithful segregation of sister chromatids. The resulting replication stress activates ATR, the major kinase involved in resolving impaired DNA replication. In addition, replication stress also activates the related kinase ATM, which is required to prevent mitotic segregation errors. However, the molecular mechanism of ATM activation by replication stress is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 48 publications
3
52
0
Order By: Relevance
“…Ubiquitinated PCNA recruits WRNIP protein, which in turn binds to the ATM activating cofactor ATMIN. This pathway is important for coordinating replication completion with cell cycle progression and, in its absence, cells enter mitosis with under-replicated DNA (Kanu et al, 2016). Finally, recent genetic experiments in yeast suggest a role for PCNA ubiquitination and TLS in Okazaki fragment maturation, at least in the context of FEN1 inactivation (Becker et al, 2015).…”
Section: Translesion Synthesismentioning
confidence: 99%
“…Ubiquitinated PCNA recruits WRNIP protein, which in turn binds to the ATM activating cofactor ATMIN. This pathway is important for coordinating replication completion with cell cycle progression and, in its absence, cells enter mitosis with under-replicated DNA (Kanu et al, 2016). Finally, recent genetic experiments in yeast suggest a role for PCNA ubiquitination and TLS in Okazaki fragment maturation, at least in the context of FEN1 inactivation (Becker et al, 2015).…”
Section: Translesion Synthesismentioning
confidence: 99%
“…In addition, WRNIP1 D37A cannot form nuclear foci after UVC irradiation nor accumulate at laser-irradiated sites. Because ubiquitylated PCNA is bound by WRNIP1, 21 it may be one of the targets of the WRNIP1 UBZ domain upon UVC or laser light irradiation.…”
Section: The Wrnip1 Gene and Structure Of The Wrnip1 Proteinmentioning
confidence: 99%
“…WRNIP1 interacts with multiple proteins involved in various cellular pathways; these include FGFR1OP (fibroblast growth factor receptor 1 oncogene partner), 28 Nup107, 29 p97/VCP, 30 RAD18, 22 ubiquitylated PCNA, 21 DNA polymerase δ, 3 DNA polymerase η, 31,32 RAD51, BRCA2, 33 ATMIN, 21 and WRN 2 . In this section, we focus on the WRNIP1-interacting proteins involved in DNA replication and/or repair: WRN, RAD18, DNA polymerase δ, and DNA polymerase η.…”
Section: Wrnip1-interacting Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ATMIN has a complementary function to NBS1: NBS1 is required for ionizing radiation-induced ATM signaling, whereas ATMIN is required for ATM activation after hypotonic or replication stress. 3,5,6 ATMIN has been shown to function in conditions of oxidative stress and aging 7 and as a transcription factor. 8 We have previously shown that ATMIN-deleted B cells (induced by CD19-Cre) have impaired class switch recombination and increased genomic instability, leading to B-cell lymphomas.…”
Section: Introductionmentioning
confidence: 99%